LOTVS: A global collection of permanent vegetation plots. (6th March 2022) - Sperandii, Marta Gaia; de Bello, Francesco; Valencia, Enrique; Götzenberger, Lars; Bazzichetto, Manuele; Galland, Thomas; E‐Vojtkó, Anna; Conti, Luisa; Adler, Peter B.; Buckley, Hannah; Danihelka, Jiří; Day, Nicola J.; et al.
Abstract: Analysing temporal patterns in plant communities is extremely important to quantify the extent and the consequences of ecological changes, especially considering the current biodiversity crisis. Long‐term data collected through the regular sampling of permanent plots represent the most accurate resource to study ecological succession, analyse the stability of a community over time and understand the mechanisms driving vegetation change. We hereby present the LOng‐Term Vegetation Sampling (LOTVS) initiative, a global collection of vegetation time‐series derived from the regular monitoring of plant species in permanent plots. With 79 data sets from five continents and 7, 789 vegetation time‐series monitored for at least 6 years and mostly on an annual basis, LOTVS possibly represents the largest collection of temporally fine‐grained vegetation time‐series derived from permanent plots and made accessible to the research community. As such, it has an outstanding potential to support innovative research in the fields of vegetation science, plant ecology and temporal ecology. Abstract : We present LOTVS, a global collection of vegetation time‐series derived from the regular monitoring of plant species using permanent plots. Currently including 79 data sets from five continents and 7, 789 time‐series monitored for at least 6 years and mostly on an annual basis, LOTVS has the potential to support timely and innovative research in vegetation science, plant ecology and temporal ecology.